STEM Education In Elementary Schools: Readiness Of PGSD Teachers In Interpreting Science And Technology From An Early Age - Widyatiningtyas, Reviandari (PT. Anagata Sembagi Education, 2025)
STEM education in elementary schools requires the pedagogical readiness of PGSD teachers as the main foundation for successful implementation. Teachers play a strategic role as facilitators connecting concepts in science, technology, engineering, and mathematics with meaningful learning experiences. However, various studies indicate that teachers' STEM literacy is still limited, particularly in integrating theory with practice, resulting in conventional learning that does not foster critical, creative, and collaborative thinking skills. Other obstacles arise from limited facilities, a lack of supporting resources, and limited access to relevant digital learning resources. Furthermore, general and unsustainable teacher training leads to low confidence in designing project-based learning. Resistance to methodological changes also slows STEM adoption, primarily due to administrative burdens and a school culture that remains solely focused on academic achievement. To address this, strategies to strengthen teacher competency are needed through practice-based training, ongoing mentoring, the development of learning communities, and the use of digital technology. Collaboration with universities and industry is also crucial in enriching teachers' STEM literacy. This study uses a qualitative literature review to map the readiness, obstacles, and strategies for strengthening PGSD teacher competency. The study results confirm that teachers' pedagogical readiness is a crucial prerequisite for STEM to truly become a means of transforming 21st-century education, not just a formal discourse.